ANALISIS PENGARUH ABU SABUT KELAPA SEBAGAI BAHAN PENGISI CAMPURAN ASPAL PADA LAPISAN AC-WC - Rosyad, Farlin; Filliandi, Ahmad Alpa (Ensiklopedia of Journal, 2024)
Coconut fiber is a durable and long-lasting material. Coconut fiber is also strong enough to withstand friction and does not break easily. Apart from that, coconut fiber is also water resistant and does not easily rot or mold. Therefore, coconut fiber could be an option when determining as a filler material in asphalt mixtures because apart from having a relatively more economical and affordable price, coconut fiber is also abundantly available. This prompted the author to conduct research using coconut fiber waste as a filler in the asphalt concrete mixture. It is hoped that the addition of coconut fiber filler can help solve the problem of puddles of water that often occur on highways. It is hoped that the use of coconut fiber as a filler material in asphalt mixtures can also be an alternative filler material used in asphalt concrete mixtures. This research was carried out with the aim of finding out the value of the marshall variable as a filling material for AC-WC layered laston and to find out how much influence coconut fiber ash as a filling material has on AC-WC layered laston in terms of the value of the marshall variable. The percentage of coconut fiber ash content used in this research was 4%, 6%, 8% and 10%. The asphalt used in this research is Pen 60-70 asphalt originating from PT. ABS (Ashpalt Bangun Sarana). This research uses the Marshall test method by reviewing the effect of coconut fiber ash on the value of the Marshall variable.Keywords: Cocounut fiber ash, AC-WC, Marshall Variable, Filler